Influence of Irrigant Activation Techniques on External Root Temperature Rise and Irrigation Penetration Depth in 3D-Printed Tooth Model: An In Vitro Study - Ali Addokhi; Ahmed Rahoma; Neveen M. A. Hanna; Faisal Alonaizan; Faraz Farooqi; Shimaa Rifaat (Dentistry Journal, 2025)
Introduction: Successful root canal therapy relies on thorough cleaning and disinfection to eliminate microorganisms and residual pulp tissue. Advanced irrigation activation techniques, including Sonic, Ultrasonic, and Diode Laser activation, have improved cleaning efficacy, bacterial reduction, smear layer removal, and irrigant hydrodynamics. On the other hand, these irrigation activation techniques may lead to a temperature rise that may risk the surrounding periodontal tissue. Thus, this study aimed to investigate the temperature rise during different irrigation activation techniques at various time intervals and evaluate the efficacy of these techniques in removing biofilm-mimicking hydrogel BMH of a simulated root canal system in 3D-printed tooth models. Methods: Ten extracted human mandibular premolars, prepared to size 40/0.04 taper, and a hundred 3D-printed resin premolars with simulated main (0.25 mm) and lateral canals (0.15 mm at 3, 7, 11 mm from apex) were used; 50 of them were filled with biofilm-mimicking hydrogel (BMH). Five irrigation activation techniques were evaluated: Diode Laser, Ultrasonic, Sonic, XP-Finisher, and Control (n = 10). Temperature rises were measured on the extracted premolars after 30 and 60 s of activation using a thermographic camera in a controlled environment (23 ± 2 °C). Irrigant penetration, with and without BMH, was assessed in 3D-printed premolars using a 2.5% sodium hypochlorite-contrast medium mixture, visualized with a CMOS radiographic sensor. Penetration was scored (main canal: 3 points; lateral canals: 0–2 points) and analyzed with non-parametric tests. Results: Diode Laser activation technique resulted in the highest temperature rise on the external root surface, followed by the Ultrasonic, with no statistically significant difference observed among the remaining groups. In terms of efficacy, Ultrasonic and Sonic activation achieved significantly greater irrigant penetration in samples without BMH, and greater BMH removal in samples with BMH, compared to Diode Laser, XP-Finisher, and Control groups. Conclusions: In this in vitro study, Diode Laser caused the highest temperature rise, followed by Ultrasonic, with significant increases from 30 to 60 s. Temperature rise did not significantly affect penetration or BMH removal. Ultrasonic and Sonic irrigation techniques achieved the highest depth of penetration (without BMH) and biofilm-mimicking Hydrogel removal (with BMH) compared to Diode Laser, XP-Finisher, and Control.